Time Driven Activity-Based Costing : Konsep Akuntansi Manajemen yang Akurat dalam Menghadapi Lingkungan yang Dinamis dan Bisnis Global - Hariyati, Hariyati (BISMA (Bisnis dan Manajemen), 2018)
This paper describes how the concept of Management Accounting, particularly the time-driven activity-based costing (TD-ABC) can be applied in calculating the cost ) is realistic. Cost becomes a very important element in calculating the earnings and net earnings were reported. The errors in the calculation of cost (cost) would result in a pricing mistake. TD-ABC is a new concept of management accounting. The emergence of TD-ABC is expected to eliminate the vulnerabilities that exist on the concept of the previous concepts such as ABC. TD-ABC concept is usually applied to companies with sophisticated accounting information systems were applicable to the Company as at the Farm Bryon ranch., Corp and Small and Medium Enterprises. Therefore it can be said TD-ABC can be applied in a dynamic environment and globalisasi and shifting corporate objective function in order to satisfy customer demand management accounting to do more